Pengaruh Efektifitas Sistem Pengendalian Intern dan Good Coorporate Governance Terhadap Kecenderungan Fraud pada Dinas Pendapatan Pengelolaan Keuangan dan Aset Daerah - Dahyuni Darwis; Rinaldy, Syiar (Insan Cita Bongaya Research Journal, 2023)
This study aims to determine the influence of the effectiveness of the internal control system and good governance on fraud tendencies in the Bantaeng Regency Regional Financial and Asset Management Revenue Office. Data collection using primary data obtained from questionnaires using purposive sampling techniques. The population is all employees of the Bantaeng Regency Financial and Asset Management Revenue Office, while the sample taken amounted to 77 respondents. The number of data analyzed was 52 data. The data analysis method uses multiple regression techniques. The results showed that the internal control system had a significant negative effect on fraud tendencies and good corporate governance had a significant negative effect on fraud tendencies.